Novel structural descriptors for automated colon cancer detection and grading. Issue 2 (September 2015) - Rathore, Saima; Hussain, Mutawarra; Aksam Iftikhar, Muhammad; Jalil, Abdul
Highlights A novel colon cancer detection and grading system has been proposed. The system exploits structural variation among various colon tissue types. The system mathematically quantifies the variation in terms of some novel features. The shape of lumen is the most discriminating factor among different tissue types. RBF kernel of SVM shows promising results for classification of colon cancer data.